g-C3N4/Fe3O4 composites synthesized via solid-state reaction and photocatalytic activity evaluation of methyl blue degradation under visible light irradiation - Ali, Asghar; Amin, Muhammad; Tahir, Muhammad; Ali, S. S.; Hussain, Asif; Ahmad, Imtiaz; Mahmood, Asif; Farooq, M. Umer; Farid, Muhammad Asim (Frontiers in Materials, 2023)
The solid-state reaction technique is used to synthesize g-C3N4, Fe3O4, and g-C3N4/Fe3O4 composites in various ratios. XRD confirmed the formation of g-C3N4, Fe3O4, and a g-C3N4/Fe3O4 heterostructure. SEM confirmed the rod-shaped structure of Fe2O3 and the layered-like fabrication of g-C3N4. The Eg of g-C3N4/Fe3O4 is about 1.9 eV, making it a beneficial composite material for visible response in photocatalysis activity, which is confirmed by UV-Vis spectroscopy. Dielectrics are used to study ferrite nanoparticles and provide us with information on the mechanism of conductivity in the parts of the dielectric that respond to an applied alternating electric field. In polycrystalline ceramics, the resistive and capacitive grains, contributions, electrode specimen interfaces, and grain boundaries may all be distinguished using impedance analysis, a crucial tool for the study of complicated electrical performance. The g-C3N4/Fe3O4 composite material shows high photocatalytic activity against MB dye.